Experimental immunologyThe influence of methisoprinol on the spleen phagocyte and blood lymphocyte activity in rats - in vitro study - Siwicki, Andrzej K.; Jung, Leszek; Małaczewska, Joanna; Wójcik, Roman (Central European Journal of Immunology, 2009)
The application of immunostimulators in human and veterinary medicine offers a wide of attractive method for inducing or modulating protection against infection diseases. In the present study we determined the in vitro influence of different concentrations of synthetic product methisoprinol on the proliferative response of blood lymphocytes stimulated by concanavaline A (ConA) and lipopolisaccharide (LPS) in rats. Also the metabolic ability and potential killing activity of spleen phagocytes were examined. For this study 10 adult male and 10 adult female rats were used. Peripheral blood was obtained by venous puncture (Vacutainer set). The proliferative ability of the blood lymphocytes stimulated by mitogens was determined by MTT assay. The respiratory burst activity (RBA) and potential killing activity (PKA) were determined by spectrophotometric assay. In each experiment, the concentrations of methisoprinol used in the RPMI 1640 medium were 0, 0.5, 1, 5, 10, 25 and 50 mg methisorinol/ml of medium. The present study shows that a concentrations between 5 to 50 mg/ml of methisoprinol statistically significantly (p < 0.05) increase the mitogens-induced proliferation rate of rats lymphocytes T and B and we have not observed statistically significant difference between male and female. The analysis of the results showed that the methisoprinol increased the metabolic ability (RBA) and potential killing activity (PKA) of spleen phagocytes at concentrations between 5 and 50 mg/ml, compared to the control. The highest RBA and PKA were observed at concentrations between 10 to 50 mg/ml and also we have not observed statistically significant difference between male and female animals.